2007
DOI: 10.1007/s11146-007-9089-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Impacts of Trails and Greenbelts on Home Price

Abstract: Amenity, Trail, Greenbelt, Home value, Hedonic estimation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 29 publications
4
44
0
2
Order By: Relevance
“…Most of the studies concentrate on the effects of large areas -urban parks, forests and greenbelts (Anthon, Thorsen, & Helles, 2004;Asabere & Huffman, 2007). Other studies pay specific attention to the inclusion of protected areas into the model in contrast to ordinary urban vegetation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the studies concentrate on the effects of large areas -urban parks, forests and greenbelts (Anthon, Thorsen, & Helles, 2004;Asabere & Huffman, 2007). Other studies pay specific attention to the inclusion of protected areas into the model in contrast to ordinary urban vegetation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also significant evidence that access to various amenities is positively associated with housing values in the community [14,16,20]. Jun and Kim [12], on the other hand, found that people were less willing to pay rent for apartments that were closer to the greenbelt in the SMA.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses aimed to estimate the effects of open spaces on real estate values have found that in general proximity to these amenities has a positive impact (Conway, et al, 2010;Lutzenhiser and Netusil, 2001). But, the influence of open space amenities on residential prices tends to decline with increasing distance (Asaber and Huffman, 2009;Jim and Chen, 2006). In addition, there is evidence that the quality of open spaces and green areas around certain property matters.…”
Section: Open Spaces and Property Valuesmentioning
confidence: 99%